Recent Reviews in Audit Practice: New Perspectives in Accounting - Tahir, Arlan (MSJ : Majority Science Journal, 2024)
Recent reviews in auditing practices have brought significant changes in the way companies manage and report their financial information. In this context, new perspectives in accounting play a key role in determining an effective and relevant audit approach. This article presents a thorough review of recent developments in audit practice and relevant new perspectives in accounting. The research method proposed to explore Recent Reviews in Audit Practice: New Perspectives in Accounting will begin with a literature review approach. This approach will make it possible to investigate and compile a strong theoretical foundation from various sources of information such as journal articles, books, research reports, and other relevant documents. The result of the study is that recent reviews in audit practice have shown a significant paradigm shift in accounting, which is influenced by technological advances and the rapid dynamics of the business environment. The adoption of advanced technologies, such as artificial intelligence and data analysis, has enabled auditors to improve efficiency and accuracy in the audit process, while a risk-based approach has helped them identify and manage relevant risks for clients. These changes require auditors to continuously improve their skills and knowledge, keeping up with technological developments and accounting-related regulations. Success in modern audit practice also depends on the ability to adapt to the rapidly changing and complex business environment.